Treatment Patterns of Cancer-associated Thrombosis in the Netherlands: The Four Cities Study - Kaptein, Fleur H.J.; Guman, Noori A.M.; Lohle, Susan B.; Klok, Frederikus A.; Mairuhu, Albert T.A.; Kamphuisen, Pieter W.; Es, Nick Van; Huisman, Menno V. (TH Open, 2024)
Background Current guidelines recommend either low-molecular weight heparin (LMWH) or direct oral anticoagulants (DOACs) as first-line treatment in cancer-associated venous thromboembolism (VTE).Aim This study aimed to investigate treatment regimens for cancer-associated VTE over the past 5 years, explore predictors for initial treatment (LMWH vs. DOAC), and to assess the risks of recurrent VTE and bleeding.Methods This was a Dutch, multicenter, retrospective cohort study including consecutive patients with cancer-associated VTE between 2017 and 2021. Treatment predictors were assessed with multivariable logistic regression models. Six-month cumulative incidences for recurrent VTE and major bleeding (MB) were estimated with death as competing risk.Results In total, 1,215 patients were included. The majority (1,134/1,192; 95%) started VTE treatment with anticoagulation: 561 LMWH (47%), 510 DOACs (43%), 27 vitamin K antagonist (2.3%), and 36 other/unknown type (3.0%). The proportion of patients primarily treated with DOACs increased from 18% (95% confidence interval [CI] 12–25) in 2017 to 70% (95% CI 62–78) in 2021. Poor performance status (adjusted odds ratio [aOR] 0.72, 95% CI 0.53–0.99) and distant metastases (aOR 0.61, 95% CI 0.45–0.82) were associated with primary treatment with LMWH. Total 6-month cumulative incidences were 6.0% (95% CI 4.8–7.5) for recurrent VTE and 7.0% (95% CI 5.7–8.6) for MB. During follow-up, 182 patients (15%) switched from LMWH to a DOAC, and 54 patients (4.4%) vice versa, for various reasons, including patient preference, recurrent thrombosis, and/or bleeding.Conclusion DOAC use in cancer-associated VTE has increased rapidly over the past years. Changes in anticoagulation regimen were frequent over time, and were often related to recurrent thrombotic and bleeding complications, illustrating the complexity and challenges of managing cancer-associated VTE.
Keywords: venous thromboembolism; anticoagulants; neoplasms; hemorrhage; cohort studies